Answer:
a = 13
b = 0
Step-by-step explanation:
Conjugate of -3 + 2i is -3 - 2i
(-3 + 2i) (-3 - 2i)
We need to expand:
9 + 6i + -6i + -4i^2
-4i^2 =(-4)(-1) = 4
9 + 4 = 13
a = 13
b = 0
Answer:
To solve this equation your goal is to get x by itself
First we need to distribute the 3 through the (2x-7)
x-6x+21=76 (-3*2x=-6x, -7*-3=21)
Your next step is to combine like terms
-5x+21=76 (x-6x=-5x)
Next subtract 21 from both sides
-5x=55 (21-21=0, 76-21=55)
Last you need to divide both sides by -5
x=-11 (-5/-5=1, 55/-5=-11)
x=-11
Hope this helps ;)
Answer:
Step-by-step explanation:
tn = a + (n-1)*d
t28 = 4 + (27)*-2 27 because 27 = 28 - 1
t28 = 4 + - 54
t28 = 4 - 54
t28 = - 50
The answer is $57.75.
Step by Step:
Take the amount of movies ( x ) multiplied by the cost of each ( $1.99 ) and add the fee. ( $8 )
Step-by-step explanation:
The constant of proportionality is the ratio of the cost to the number of pounds of walnuts. In other words, it is the price of one pound of walnuts.
$10.92 / 4 lb = $2.73 / lb